Serum insulin-like growth factor-I is positively associated with serum prostate-specific antigen in middle-aged men without evidence of prostate cancer. - Oliver, SE; Barrass, B; Gunnell, D; Donovan, J; Peters, T; Persad, R; Gillatt, D; Neal, D; Hamdy, F; Holly, J (2004)
We have examined the relationship between serum insulin-like growth factor-I (IGF-I) and prostate-specific antigen in 367 healthy men without evidence of prostate cancer and found a positive association (P = 0.05). In men without prostate cancer, serum prostate-specific antigen is closely related to prostate size, and our findings, therefore, suggest that IGF-I may induce prostatic epithelial proliferation. Higher circulating levels of IGF-I have been associated with increased risk of both prostate cancer and possibly benign prostatic hyperplasia. Greater rates of cell proliferation induced by IGF-I may be a key biological pathway underlying these disorders.